Pembelajaran Lesson Study Dalam Meningkatkan Aktivitas Kolaborasi Antar Siswa - Pasongli, Hernita; Hamid, Fatma; Marthinu, Eva; Atua, Naomi (Universitas Negeri Makassar, 2021)
Collaboration in learning is often carried out by students, but often the teacher does not evaluate it, the teacher assumes that the collaboration carried out by students in learning is just an ordinary interaction and rarely gives students the opportunity to ask questions, differentiates abilities and reduces learning opportunities together, so students do not learn from peers and do not have the opportunity to provide input and respect the opinions of others. This problem then becomes the objective of implementing Lesson Study learning to find out how much collaborative activity between students in learning.Â The main purpose of implementing Lesson Study in these subjects is to increase collaboration activities among students. The research team is interested in implementing learning through lesson study. The basic pattern of lesson study is the heterogeneous grouping of students in small groups with four members. The members are expected to share knowledge each other through sharing tasks given by the teacher. The task is continued with jumping tasks. That is, giving tasks / questions that increase without giving examples first. If a third of students can work on the question, then the jumping task is successful. The method used is descriptive. The data collection techniques were documentation and observation. The data analysis used was descriptive. The results showed that there was an increase in student collaboration activities when implementing lesson study, it was 25%.